The Perceptions between Teachers’ in Public and Private Schools related to the (LFH) Learn from Home Policy - Sari Wahyuni; Ariyanti Ariyanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Knowledge of the various kinds of teacher perceptions between 2 different schools about LFH policies will increase our knowledge of each teacher's strengths and weaknesses in learning activities using LFH policies during the pandemic. This research was conducted in private schools SD Darul Falah 2 Samarinda and public schools SDN 019 Muara Badak, namely four teachers and two principals. It collected data in this study using interview techniques to determine the strengths and weaknesses of LFH policies from teacher perceptions of LFH policies and questionnaire techniques to support interviews with teachers. Furthermore, The results showed that 24% of private school teachers' perceptions of the LFH policy were included in the